Old Believers of the Yenisei and Shoriya: an entangled structure of a “plain” society - Rygovskiy, Danila S. (The New Research of Tuva, 2019)
The article discusses entangled social structure of Chasovennye Old Believers living along the Yenisei (i. e. in Tuva and Krasnoyarsk krai) and in Mountain Shoriya. This study is based on field materials collected by the author; some excerpts from interlocutors’ talks are provided, as well as from some archival documents and published ethnographic materials.The author shows that entangled and controversial social structure of Enisey and Mountain Shoriya Old Believers lies beyong the nominal belonging to a confessional group. This structural nonuniformity is shaped by issues of ritual purity, kinship and religious practices. The study of communities in the abovementioned locations reveals a range of possible interpretations of these issues, which in their turn produce alternative and competing hierarchies within the same group. These hierarchies can potentially generate a future split.Though diversified groups sometimes are considered as different factions, they still can maintain a sort of unity. Splits do not reduce the sense of congeniality of religious groups. In due course, traces of the spilt disappear as it happened in Tuva.
Keywords: Old Believers; Tuva; Enisey; Krasnoyarsk krai; Mountain Shoriya; Chasovennye faction; social structure; ritual purity; religious practices; matrimonial relationship